2018
DOI: 10.1111/cxo.12566
|View full text |Cite
|
Sign up to set email alerts
|

Scotopic contrast sensitivity and glare after accelerated corneal cross‐linking

Abstract: Background:The aim was to assess one-year changes in uncorrected and corrected contrast sensitivity (CS) and glare under scotopic conditions after accelerated cross-linking (CXL) using the 18 mW/cm 2 protocol for the treatment of progressive keratoconus and compare results with unoperated controls. Methods: In this non-randomised clinical trial, 30 eyes were enrolled in the CXL group and 30 were assigned to the control group. Scotopic CS at spatial frequencies (SFs) of 0.5, 1.1, 2.2, 3.4, 7.1 and 15 cycles per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The contrast sensitivity was tested using the same vision monitor. The testing protocol has been described in detail previously [ 16 ]. The test was performed monocularly at a distance of 2 m under corrected and uncorrected conditions after adapting to darkness for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The contrast sensitivity was tested using the same vision monitor. The testing protocol has been described in detail previously [ 16 ]. The test was performed monocularly at a distance of 2 m under corrected and uncorrected conditions after adapting to darkness for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Also, we showed that the improvement of lower spatial frequencies is related to baseline values and not to CXL [ 19 ]. In this report, linear regression model appeared that baseline values lead to CS improvement not CXL protocols.…”
Section: Discussionmentioning
confidence: 99%